2012
DOI: 10.1111/j.1467-7660.2012.01781.x
|View full text |Cite
|
Sign up to set email alerts
|

The IMF, the World Bank, and the Global Economic Crisis: Exploring Paradigm Continuity

Abstract: A thematic examination of the IMF and the World Bank's recent crisis programmes finds strong evidence of prescriptive continuity with the pre‐crisis repertoire of these organizations, contradicting their legacy of policy adaptation during times of systemic turbulence. How are we to account for this anomaly? The current specialist literature on the Fund and Bank offers plausible explanations, mainly by stressing principal–agent relations and intra‐organizational dynamics. Yet these lender‐oriented approaches ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(29 citation statements)
references
References 81 publications
(70 reference statements)
0
29
0
Order By: Relevance
“…Referring to an IMF study from 2009, researchers concluded that 'the IMF's claim that programmes now "creat[e] policy space" by exhibiting "responsive design and streamlined conditionality"' is not accurate (Kentikelenis et al 2016: 24). Other studies by academics (Gabor 2010;Güven 2012), IOs (Ortiz and Cummins 2013), and nongovernmental organizations (Griffiths and Todoulos 2014;Muchhala 2011;Weisbrot et al 2009) have reached similar conclusions.…”
Section: The Imf Country-level Work and Loan Conditionalitiesmentioning
confidence: 57%
“…Referring to an IMF study from 2009, researchers concluded that 'the IMF's claim that programmes now "creat[e] policy space" by exhibiting "responsive design and streamlined conditionality"' is not accurate (Kentikelenis et al 2016: 24). Other studies by academics (Gabor 2010;Güven 2012), IOs (Ortiz and Cummins 2013), and nongovernmental organizations (Griffiths and Todoulos 2014;Muchhala 2011;Weisbrot et al 2009) have reached similar conclusions.…”
Section: The Imf Country-level Work and Loan Conditionalitiesmentioning
confidence: 57%
“…In surveying the post‐crisis literature on the World Bank and the IMF for Development and Change , Güven contends that existing literature explains the limited or even non‐existent nature of change in the traditional BWIs by ‘stressing principal–agent relations and intra‐organizational dynamics’ (Güven, : 869). He rightly advocates that scholars should not only focus on the supply or lender side of global economic governance, but also on the demand for loans from borrow countries.…”
Section: Old Dogs New Tricks?mentioning
confidence: 99%
“…In other words, in these cases, state failure is considered to be a far greater problem than the market failures that intervention seeks to correct. This view has not changed dramatically even in light of the 2008 crisis (Guven, ).…”
Section: The Role Of Finance In the Developmental Statementioning
confidence: 99%